2005
DOI: 10.1016/j.nuclphysb.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The M2–M5 brane system and a generalized Nahm's equation

Abstract: We propose an equation that describes M2-branes ending on M5-branes, and which generalizes the description of the D1-D3 system via Nahm's equation. The simplest solution to this equation constructs the transverse geometry in terms of a fuzzy three sphere. We show that the solution passes a number of consistency checks including a calculation of the energy of the system, matching to the self-dual string solution in the M5-brane world volume, and a study of simple fluctuations about the ground state configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
379
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(386 citation statements)
references
References 34 publications
6
379
0
1
Order By: Relevance
“…Their model, that incorporates insights from previous papers [12] [13], includes half-BPS fuzzy 3-sphere solitons. This solutions were argued by Basu and Harvey [14] to provide the M2-branes worldvolume description of the multiple M2-branes ending on an M5-brane, generalizing a similar mechanism studied for the D1-D3 system [15]. The Bagger-Lambert theory is a 3-dimensional N = 8 supersymmetric field theory, based on a novel algebraic structure, dubbed 3-algebra.…”
Section: Introduction and Discussionmentioning
confidence: 68%
“…Their model, that incorporates insights from previous papers [12] [13], includes half-BPS fuzzy 3-sphere solitons. This solutions were argued by Basu and Harvey [14] to provide the M2-branes worldvolume description of the multiple M2-branes ending on an M5-brane, generalizing a similar mechanism studied for the D1-D3 system [15]. The Bagger-Lambert theory is a 3-dimensional N = 8 supersymmetric field theory, based on a novel algebraic structure, dubbed 3-algebra.…”
Section: Introduction and Discussionmentioning
confidence: 68%
“…Another thing that could be interesting to check is whether the generalized Nahm equation for the self-dual string, that was proposed in [14], can be related to the Nahm equation [15] via the Hopf map, in a similar fashion as we have related the Bogomolnyi equations to each other in this paper.…”
Section: Jhep12(2006)066mentioning
confidence: 75%
“…The work of Bagger and Lambert [1][2] [3], and Gustavsson [4] [5], following earlier work [6] [7], showed that a manifestly supersymmetric and SO (8) invariant Lagrangian can be constructed given a "three-algebra," a generalization of a Lie algebra based on an antisymmetric triple product structure. It seemed plausible that the worldvolume theory of coincident M2-branes should lie somewhere in this class of theories.…”
Section: Introductionmentioning
confidence: 99%
“…We show that the combined action is symmetric under a BRST 5 The details of the orbifold depend on a discrete parameter that is present in the theory, the level associated with a Chern-Simons term. 6 The fact that the algebras in [13][14] [15] are the unique undecomposable three-algebras has been proven in [17].…”
Section: Introductionmentioning
confidence: 99%